Plan de emprendimiento para la creación de una pyme distribuidora de productos de consumo masivo en la ciudad de Machala. - Salvatierra Minango, Hugo Enrique (2017)
For the present research work was carried out a study for the Creation of a SME Distributor of Massive consumer products in the city of Machala, which will allow to market the merchandise in all points of the locality, and to provide a quality service. By conducting the market study, it was possible to determine that 81% of the respondents agree to the creation of a distributor of exclusive yoghurt products Chivería and Facundo in Machala, so we do not currently have any distributors that Commercialize the aforementioned products in this locality, with a great opportunity of business and profitability. The location of the Distributor will be in the city of Machala in the streets Ave. 11ava Norte and Vía Limón, which is a place where there is sufficient space both internal and external for the logistics of the products and in turn the supply and discharge of the Merchandise without interfering with vehicular traffic. It is important to mention that there is a good reception of yogurt to market and knowledge of the brand, for its quality and flavor of the product, which in the survey indicated that they would like to have this product in the neighborhood stores of each sector located in the city. We have good expectations in the results of the surveys conducted in the city, which we have various opportunities to grow as a company and to expand to other locations around Machala. And to all this, you must do a thorough job with people who put love and sweat to the shirt they are going to represent. The development of creating a distributor with a name and logo that identifies the company goes beyond just marketing the products. Our idea is to give a quality service where our clients recognize us in the human part of each of the members that represent this distributor, that we are excellent people and of high honesty, responsibility and seriousness in what we do, at the moment of giving A service, and thus be different to the competition which we prefer for everything mentioned above. The realization of the project is completely acceptable in terms of its resource and investment since these items are the most desirable in this purpose to create a distributor, for which it has been perfected to reduce the impact caused by the weaknesses detected in the analysis, for Our proposal is consistent with the theme of location, infrastructure, design, mission, vision, values, structures, strategic objectives, marketing process, investment and financing, executing through an economic and financial analysis of the cost benefit to Short term and long term which shows us that the present research project is viable. In the last request, it is determined the impacts, indications and positive or negative aspects that the implementation of the project will induce in a certain area, by which it was possible to establish the conclusions and recommendations of the research carried out.